Bionic Adaptive Thin‐Membranes Sensory System Based on Microspring Effect for High‐Sensitive Airflow Perception and Noncontact Manipulation. (26th July 2021) - Zhou, Wei; Xiao, Peng; Liang, Yun; Wang, Qiling; Liu, Depeng; Yang, Qing; Chen, Jianhua; Nie, Yujing; Kuo, Shiao‐Wei; Chen, Tao
Abstract: Recently airflow sensors based on mechanical deformation mechanisms have drawn extensive attention due to their favorable flexibility and sensitivity. However, the fabrication of highly sensitive and self‐adaptive airflow sensors in a simple, controllable, and scalable method still remains a challenge. Herein, inspired by the wing membrane of a bat, a highly sensitive and adaptive graphene/single‐walled nanotubes‐Ecoflex membrane (GSEM) based airflow sensor mediated by the reversible microspring effect is developed. The fabricated GSEM is endowed with an ultralow airflow velocity detection limit (0.0176 m s −1 ), a fast response time (≈1.04 s), and recovery time (≈1.28 s). The GSEM‐based airflow sensor can be employed to realize noncontact manipulation. It is applied to a smart window system to realize the intelligent, open, and close behaviors via a threshold control. In addition, an array of airflow sensors is effectively designed to differentiate the magnitude and spatial distribution of the applied airflow stimulus. The GSEM‐based airflow sensor is further integrated into a wireless vehicle model system, which can sensitively capture the flow velocity information to realize a real‐time direction of motion manipulation. The microspring effect‐based airflow sensing system shows significant potentials in the fields of wearable electronics and noncontact intelligent manipulation. Abstract : A flexible and adaptable airflow sensor enabled by a bioinspired thin‐membrane based on a reversible microspring effect is described. The graphene/single‐walled nanotubes structured thin membrane can respond rapidly and sensitively to applied airflow with ultralow detection limit, fast response time, and wide working range. Furthermore, a smart window and wireless vehicle are carefully designed to realize airflow‐controlled noncontact manipulation.